Thermal interface material with liquid metal dynamic bonds, preparation method and test method
By using coupling agents to modify the surface of the metal filler in liquid metal composite materials, the problems of limited thermal conductivity and solid-liquid separation are solved, and the preparation of liquid metal thermal interface materials with high thermal conductivity and low thermal resistance are achieved.
Patent Information
- Application Number
- CN202510459247.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-14
- Publication Date
- 2025-08-01
AI Technical Summary
The thermal conductivity of existing liquid metal composite materials is limited, has low viscosity and is prone to solid-liquid separation, and it is difficult to apply and print.
The metal filler surface is modified with coupling agent, the number of lonely electron pairs is increased, the liquid metal dynamic bond is formed, the viscosity is increased, and the liquid metal thermal interface material is prepared through a vacuum stirring process.
It significantly improves the thermal conductivity and viscosity of liquid metal thermal interface materials, reduces the interface thermal resistance, reduces solid-liquid separation, reduces the preparation cost, and avoids the Pump-out phenomenon.
Smart Images

Figure CN120399647A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of preparation of liquid metal thermal interface materials, and particularly to liquid metal thermal interface materials, preparation methods and testing methods. Background Art
[0002] Liquid metal composites are mostly formed by mixing liquid metal and thermal conductive fillers through methods such as ball milling or grinding.
[0003] The current defects of this composite material are as follows: 1. The thermal conductivity of the composite material is limited by the thermal conductivity of the liquid metal itself and cannot be further improved. 2. The viscosity of the composite material is relatively low, and there are certain difficulties in coating and printing. 3. The prepared liquid metal composite material still has a certain solid-liquid separation phenomenon. Summary of the Invention
[0004] Based on this, a thermal interface material with liquid metal dynamic bonds is provided, which is beneficial to obtaining higher thermal conductivity, better viscosity and not easily showing solid-liquid separation phenomenon.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] A thermal interface material with liquid metal dynamic bonds, the liquid metal thermal interface material includes the following components in parts by weight:
[0007] Liquid metal: 50 - 90 parts, thermal conductive filler: 10 - 30 parts, metal filler: 5 - 20 parts, coupling agent:
[0008] 0.1 - 0.3 parts,
[0009] The metal filler is used to reduce the interfacial thermal resistance. The surface of the metal filler is modified by the coupling agent. The addition of the coupling agent directionally increases the groups on the surface of the metal filler, increases the number of lone electron pairs, which is beneficial to the formation of liquid metal dynamic bonds, and increases the interaction force between the liquid metal and the thermal conductive powder to increase the viscosity.
[0010] In one embodiment, the liquid metal is one or more of alloys such as gallium-based, bismuth-based, indium-based, tin-based, etc.
[0011] In one embodiment, the thermal conductive filler is one or more of aluminum nitride, aluminum oxide, zinc oxide, boron nitride, silicon carbide, magnesium oxide, silicon dioxide, calcium carbonate, magnesium sulfate, diamond, boron carbide, silicon nitride, and its particle size is 0.1 - 30um.
[0012] In one embodiment, the metal filler is one or more of silver powder, nickel powder, copper powder, aluminum powder, silver-plated aluminum powder, silver-plated copper powder, silver-plated nickel powder, iron powder, etc., and its particle size is 0.5 - 30um.
[0013] In one embodiment, the coupling agent is one or more of an alkylsiloxane coupling agent, an aminosiloxane coupling agent, an alkylsilazane coupling agent, and an aminosilazane coupling agent. In one embodiment, the volume percentage of the liquid metal is 65%-75%.
[0014] A method for preparing a liquid metal thermal interface material for preparing the liquid metal thermal interface material specifically includes: performing interface modification on metal fillers through a coupling agent,
[0015] mixing and stirring the thermal conductive fillers and the metal fillers after interface modification, then adding the liquid metal and mixing and stirring, heating, and stirring under vacuum conditions. After the stirring is completed, a liquid metal thermal interface material is obtained.
[0016] In one embodiment, it further includes a step of judging whether the thermal conductive filler is qualified. Add the thermal conductive filler to the liquid metal, heat it to more than 10°C above the melting point of the liquid metal, stir under vacuum conditions, and control the stirring time to avoid spontaneous combustion due to overheating of the mixture. After the stirring time arrives, the mixture is in a paste state and there is no solid-liquid separation, indicating that the thermal conductive filler is a qualified thermal conductive filler.
[0017] In one embodiment, the performing interface modification on metal fillers through a coupling agent specifically includes: mixing the metal fillers, the coupling agent, and absolute ethanol, then heating and stirring, and then performing filtration, washing, and drying steps.
[0018] A testing method for a liquid metal thermal interface material includes the liquid metal thermal interface material,
[0019] Apply the prepared liquid metal thermal interface material on the base, place the base in a thermal shock chamber, the low temperature of the test temperature is -40°C, the high temperature is 125°C, and continuously perform thermal shock on the liquid metal thermal interface material on the base in the thermal shock chamber for 10 to 20 days.
[0020] The beneficial effects of this application are:
[0021] (1) By using the method of interface modification on the surface of metal fillers, the groups on the surface of metal fillers are increased directionally, the number of lone electron pairs such as N, O, and S is increased, which is beneficial to the formation of dynamic bonds of liquid metal, increases the interaction force between the liquid metal and the metal fillers, thereby increasing the viscosity of the liquid metal thermal interface material, and thus is beneficial to the application of the liquid metal thermal interface material on the device.
[0022] (2) The combined effect of the metal filler and the thermal conductive filler increases the thermal conductivity of the liquid metal thermal interface material and reduces the interface thermal resistance. Compared with the liquid metal composite material without adding the metal filler, the material of this application can increase the thermal conductivity by at least 20%. In some preferred cases, it can be increased by 37% or even higher.
[0023] (3) Traditional processes such as mechanical stirring, ball milling, and grinding. This method forms a coordination effect between the liquid metal and the thermal conductive filler through the mechanochemical force induced by long-term mechanical shearing. In this invention, through the directional screening of the coupling agent, the time for the formation of dynamic bonds in the liquid metal is further reduced, thereby effectively reducing the preparation time of the material during the preparation process, and thus significantly reducing the preparation cost of the material.
[0024] (4) The thermal interface material prepared from the gallium-based liquid metal of this application hardly exhibits the Pump-out phenomenon.
[0025] (5) The thermal interface material prepared from the bismuth-based liquid metal of this application has almost no corrosiveness to metal aluminum devices. Description of the Drawings
[0026] Figure 1 It is a schematic diagram of the liquid metal thermal interface material prepared in the embodiment of this application.
[0027] Figure 2 It is a DSC curve diagram of the gallium-based liquid metal Galinstan in the embodiment of this application.
[0028] Figure 3 It is a schematic diagram after applying the liquid metal thermal interface material prepared from the gallium-based liquid metal in the embodiment of this application.
[0029] Figure 4 It is a schematic diagram of the preparation method of the liquid metal thermal interface material in the embodiment of this application.
[0030] Figure 5 It is a schematic diagram of the test result of the corrosion resistance test of the liquid metal thermal interface material in the embodiment of this application.
[0031] Figure 6 It is a schematic diagram of the test result of the Pump-out test on the liquid metal thermal interface material prepared from the gallium-based liquid metal in the embodiment of this application. Detailed Embodiments
[0032] To make the above objects, features, and advantages of the present invention more obvious and understandable, the following detailed description of the specific embodiments of the present invention will be given in conjunction with the accompanying drawings.
[0033] The present application provides a thermal interface material with liquid metal dynamic bonds, comprising the following components in parts by weight: liquid metal: 50-90 parts, for example, it can be 50-60 parts, 60-70 parts, 70-80 parts, 80-90 parts, etc.; thermal conductive filler: 10-30 parts, for example, it can be 10-15 parts, 15-30 parts, etc.; metal filler: 5-20 parts, for example, it can be 5-10 parts, 10-15 parts, 15-20 parts, etc.; coupling agent: 0.1-0.3 parts, for example, it can be 0.1-0.2 parts, 0.2-0.3 parts, etc.
[0034] The above metal filler is used to reduce the interfacial thermal resistance. The surface of the metal filler is modified with a coupling agent. The addition of the coupling agent increases the groups on the surface of the metal filler directionally, increases the number of lone electron pairs, which is beneficial to the formation of liquid metal dynamic bonds, and increases the interaction force between the liquid metal and the thermal conductive powder to increase the viscosity.
[0035] Specifically, the liquid metal is one or more of alloys such as gallium-based, bismuth-based, indium-based, tin-based, etc., and its melting point is 5-70 °C. The thermal conductive filler is one or more of aluminum nitride, aluminum oxide, zinc oxide, boron nitride, silicon carbide, magnesium oxide, silicon dioxide, calcium carbonate, magnesium sulfate, diamond, boron carbide, silicon nitride, etc., and its particle size is 0.1-30 μm. The metal filler is one or more of silver powder, silver-nickel alloy, nickel powder, copper powder, aluminum powder, silver-plated aluminum powder, silver-plated copper powder, silver-plated nickel powder, iron powder, etc., and its particle size is 0.5-30 μm. The coupling agent is one or more of alkyl siloxane coupling agent, amino siloxane coupling agent, alkyl silazane coupling agent, amino silazane coupling agent. The volume ratio of the liquid metal is 65%-75%.
[0036] The following further details the liquid metal thermal interface material and its preparation method of the present application through specific examples and comparative examples.
[0037] Example 1
[0038] A liquid metal thermal interface material uses the following raw materials:
[0039] The raw material of the liquid metal is a gallium-indium-tin alloy, and the mass percentages of gallium, indium, and tin are 68.5%: 21.5%: 10%. The melting point of the liquid metal is 9.1 °C, see Figure 2 ,
[0040] The thermal conductive filler is AlN, and the metal filler is silver-plated nickel powder. The D50 particle size of AlN is 1 μm, and the D50 particle size of the silver-plated nickel powder is 12 μm. The volume fraction of the powder formed by the thermal conductive filler and the metal filler is 24.5%.
[0041] The coupling agent is an amino coupling agent, and the amino coupling agent is N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.
[0042] The specific preparation steps are as follows:
[0043] S1: Preparation of gallium-based liquid metal
[0044] Put metallic gallium in a sealed flask according to the ratio, and place it in a water bath at 55 °C. Under constant temperature, heat it in the air for 25 minutes to obtain liquid gallium. Then, add indium and tin metals according to the ratio, and under the condition of a temperature of 55 °C and anaerobic conditions, stir constantly for 3 hours to obtain gallium-based liquid metal.
[0045] S2: Interface modification of metal fillers
[0046] Dry the silver-plated nickel powder in advance. Stir a small amount of amino coupling agent and 50 ml of absolute ethanol evenly by mechanical stirring, then add the silver-plated nickel powder, with a stirring rate of 200 rpm / min and a stirring time of 2 hours; then filter, wash, and dry to obtain the silver-plated nickel powder with interface modification.
[0047] S3: Preparation of gallium-based liquid metal paste
[0048] Due to the characteristics of the AlN powder itself, the surface of the powder must be modified before leaving the factory to prevent the decomposition of AlN. Therefore, no secondary treatment is performed on AlN. Mix and stir 2.5 g of AlN powder and 1.5 g of the silver-plated nickel powder described in step S2 to obtain a mixed powder A. Then, add 18 g of gallium-based liquid metal to the mixed powder A and mix and stir, heat to 20 °C, stir in a vacuum for 20 minutes, with a stirring speed of 1100 rpm / min. After stirring is completed, gallium-based liquid metal paste is obtained.
[0049] This embodiment also includes a method for screening AlN powder, and the specific steps are as follows:
[0050] Respectively take 1 g of AlN powder produced by different manufacturers and add it to 9 g of liquid metal, heat to above the melting point of the liquid metal by 10 °C, stir in a vacuum for 5 minutes, with a stirring speed of 1100 rpm / min. Note that the stirring time should not be too long, otherwise the powder will overheat and catch fire. At this time, if the sample is in a paste state, it means that the AlN powder is suitable for use in liquid metal thermal interface materials, as shown in Figure 1 (a). If the sample is in a solid-liquid separation state, it means that the AlN powder is not suitable for use in liquid metal thermal interface materials, as shown in Figure 1 (b).
[0051] Comparative Example 1
[0052] A liquid metal thermal interface material, the raw materials include:
[0053] The raw material of the liquid metal is gallium, indium and tin alloy, and the mass percentage of gallium, indium and tin is 68.5%:21.5%:10%. The melting point of the liquid metal is 9.1℃. Figure 2 ,
[0054] The thermal conductive filler is AlN, wherein the D50 particle size of the AlN is 1 μm, and the volume fraction of the thermal conductive filler powder is 24.5%.
[0055] The specific preparation method is as follows:
[0056] S1: Preparation of gallium-based liquid metal;
[0057] Metal gallium is placed in a sealed flask according to the ratio and placed in a water bath at 55°C. Liquid gallium is obtained after heating in air at a constant temperature for 25 minutes. After that, indium and tin metals are added according to the ratio. Gallium-based liquid metal is obtained after constant temperature stirring for 3 hours at a temperature of 55°C and in an oxygen-free condition.
[0058] S2: Preparation of gallium-based liquid metal paste;
[0059] 4 g of AlN powder and 22 g of gallium-based liquid metal were mixed and stirred under vacuum conditions for 20 min at a stirring speed of 1100 rpm / min to obtain a gallium-based liquid metal paste.
[0060] Example 2
[0061] A liquid metal thermal interface material, the raw materials used include:
[0062] The raw material of the liquid metal is gallium, indium and tin alloy, and the mass percentage of gallium, indium and tin is 68.5%:21.5%:10%. The melting point of the liquid metal is 9.1℃. Figure 2 .
[0063] The thermal conductive filler is Al2O3, wherein the D50 particle size of Al2O3 is 2 μm, the metal filler is silver-plated nickel powder, and the D50 particle size of the silver-plated nickel powder is 12 μm. The volume fraction of the powder formed by the thermal conductive filler and the metal filler is 35%.
[0064] The coupling agent is an amino coupling agent, and the amino coupling agent is KH-550 ( γ -aminopropyltriethoxysilane).
[0065] The specific preparation steps are as follows:
[0066] S1: Preparation of Gallium-based Liquid Metal,
[0067] Put gallium metal in a sealed flask according to the ratio, and place it in a water bath at 55 °C. Under the constant temperature condition, heat it in the air for 25 minutes to obtain liquid gallium. Then, add indium and tin metals according to the ratio, and under the condition of a temperature of 55 °C and no oxygen, stir constantly for 3 hours to obtain the gallium-based liquid metal.
[0068] S2: Interface modification of the thermal conductive powder
[0069] Dry the silver-plated nickel powder in advance. Stir a small amount of amino coupling agent and 50 ml of absolute ethanol evenly by mechanical stirring, then add the silver-plated nickel powder, with a stirring rate of 200 rpm / min and a stirring time of 2 hours; then filter, wash, and dry to obtain the silver-plated nickel powder with interface modification.
[0070] Dry the Al2O3 powder in advance. Stir a small amount of amino coupling agent and 50 ml of absolute ethanol evenly by mechanical stirring, then add the Al2O3 powder, with a stirring rate of 200 rpm / min and a stirring time of 2 hours; then filter, wash, and dry to obtain the Al2O3 powder with interface modification.
[0071] S3: Preparation of the gallium-based liquid metal paste
[0072] Mix and stir 4 g of Al2O3 powder and 2 g of silver-plated nickel powder in step S2 to obtain the mixed powder A. Then add 14 g of gallium-based liquid metal to the mixed powder A and mix and stir, heat to 20 °C, stir for 20 minutes under vacuum conditions, with a stirring speed of 1100 rpm / min, and obtain the gallium-based liquid metal paste after stirring is completed.
[0073] Comparative Example 2 [[ID=2"]]
[0074] A liquid metal thermal interface material, the raw materials include:
[0075] The raw material of the liquid metal is a gallium-indium-tin alloy, and the mass percentages of gallium, indium, and tin are 68.5%: 21.5%: 10%. The melting point of the liquid metal is 9.1 °C, see Figure 2 .
[0076] The thermal conductive filler is Al2O3, where the D50 particle size of Al2O3 is 2 μm, and the volume fraction of the powder formed by the thermal conductive filler is 35%.
[0077] The specific preparation steps are as follows:
[0078] S1: Preparation of the gallium-based liquid metal
[0079] Put gallium metal in a sealed flask according to the ratio, and place it in a water bath at 55 °C. Under the constant temperature condition, heat it in the air for 25 minutes to obtain liquid gallium. Then, add indium and tin metals according to the ratio, and under the condition of a temperature of 55 °C and no oxygen, stir constantly for 3 hours to obtain the gallium-based liquid metal.
[0080] S2: Preparation of gallium-based liquid metal paste,
[0081] Mix and stir 6 g of Al2O3 powder and 14 g of gallium-based liquid metal, stir for 20 minutes under vacuum conditions, and the stirring speed is 1100 rpm / min. After stirring, the gallium-based liquid metal paste is obtained.
[0082] Example 3
[0083] A liquid metal thermal interface material, the raw materials include:
[0084] The raw material of the liquid metal is bismuth-indium-tin alloy, and the mass percentages of bismuth, indium, and tin are 50%:25%:25%. The melting point of the liquid metal is 60 °C.
[0085] The thermal conductive filler is Al2O3, the D50 particle size of Al2O3 is 2 μm, the metal filler is silver-plated nickel powder, the D50 particle size of the silver-plated nickel powder is 12 μm, and the volume fraction of the powder formed by the thermal conductive filler and the metal filler is 35%.
[0086] The coupling agent is an amino coupling agent, and the amino coupling agent is KH-550.
[0087] The specific preparation steps are as follows:
[0088] S1: Preparation of bismuth-based liquid metal,
[0089] Put the raw materials bismuth, indium, and tin metals into a quartz crucible according to the ratio. Under an oxygen-free environment, slowly heat to 300 - 350 °C, and mechanically stir for 1 - 2 hours. Pour the molten alloy into a preheated metal mold and quickly cool to obtain the bismuth-based liquid metal.
[0090] S2: Interface modification of the thermal conductive powder,
[0091] Dry the silver-plated nickel powder in advance. Stir a small amount of amino coupling agent and 50 ml of absolute ethanol evenly by mechanical stirring, then add the silver-plated nickel powder, the stirring rate is 200 rpm / min, and the stirring time is 2 h; then filter, wash, and dry to obtain the interface-modified silver-plated nickel powder.
[0092] Dry the Al2O3 powder in advance. Mix a small amount of amino coupling agent with 50 ml of absolute ethanol evenly by mechanical stirring, then add the Al2O3 powder, with a stirring rate of 200 rpm / min and a stirring time of 2 h; then filter, wash, and dry to obtain the interface-modified Al2O3 powder.
[0093] S3: Preparation of bismuth-based liquid metal phase change sheet
[0094] Mix and stir 6 g of Al2O3 powder and 2 g of the silver-plated nickel powder in step S2 to obtain a mixed powder A. Then add 27.3 g of bismuth-based liquid metal to the mixed powder A and mix and stir, heat to 70 °C, stir for 20 min under vacuum conditions, with a stirring temperature of 70 °C and a stirring speed of 1100 rpm / min. After stirring, a bismuth-based liquid metal phase change sheet is obtained, as Figure 1 (c) shown.
[0095] Comparative Example 3
[0096] A liquid metal thermal interface material, the raw materials include:
[0097] The raw material of the liquid metal is a bismuth-indium-tin alloy, and the mass percentages of bismuth, indium, and tin are 50%:25%:25%. The melting point of the liquid metal is 60 °C.
[0098] The thermal conductive filler is Al2O3, where the D50 particle size of Al2O3 is 2 μm, and the volume fraction of the powder formed by the thermal conductive filler is 35%.
[0099] The specific preparation steps are as follows:
[0100] S1: Preparation of bismuth-based liquid metal
[0101] Put the raw materials bismuth, indium, and tin metals into a quartz crucible according to the ratio, in an oxygen-free environment, slowly heat to 300 - 350 °C, mechanically stir for 1 - 2 hours, and pour the molten alloy into a preheated metal mold and quickly cool to obtain bismuth-based liquid metal.
[0102] S2: Preparation of bismuth-based liquid metal phase change sheet
[0103] Mix and stir 6 g of Al2O3 powder and 23.8 g of bismuth-based liquid metal, stir for 20 min under vacuum conditions, with a stirring temperature of 70 °C and a stirring speed of 1100 rpm / min. After stirring, a bismuth-based liquid metal phase change sheet is obtained.
[0104] This application evaluated the performance of the materials prepared in the above various experiments.
[0105] 1. Thermal conductivity test method: The test standard is ASTM D 5470, and the thermal conductivity is measured by the LonGwin three-thickness method.
[0106] 2. Interfacial thermal resistance test method: The test standard is ASTM D 5470, and the interfacial thermal resistance is measured by LonGwin.
[0107] 3. Viscosity test method: It is tested by a TA rheometer at a rotation speed of 1 Hz.
[0108] 4. Pump-out performance test method: A thermal shock chamber is used, with the conditions of low temperature -40°C and high temperature 125°C, and continuous thermal shock for 14 days.
[0109] The performance tests were carried out on Examples 1-3 and Comparative Examples 1-3, and the test data are shown in Table 1 below.
[0110] Table 1 Performance test results of Examples 1-3 and Comparative Examples 1-3
[0111]
[0112]
[0113] It can be seen from Table 1 that the thermal conductivity of Example 1 of the present application is increased by 21% compared with Comparative Example 1, the thermal resistance is reduced by 31%, and the viscosity is increased by 18%. The thermal conductivity of Example 2 is increased by 37% compared with Comparative Example 2, the thermal resistance is reduced by 44%, and the viscosity is increased by 322%. The thermal conductivity of Example 3 is increased by 27% compared with Comparative Example 3, the thermal resistance is reduced by 45%, and the viscosity is increased by 75%. This fully shows that by adding metal fillers and coupling agents, the thermal conductivity and viscosity of the material can be significantly improved, and at the same time, the thermal resistance can be significantly reduced.
[0114] The present application also conducted corrosion resistance tests and Pump-out experiments.
[0115] As Figure 5 shown, liquid metals have been widely studied for their excellent thermal conductivity, but gallium metal reacts with certain metals, such as aluminum and copper, to form intermetallic compounds, thus damaging the device and has been restricted. Therefore, corrosion tests were carried out on Example 1 and Example 3. The specific method is as follows. The liquid metal thermal interface material is applied between metal blocks and placed at room temperature for a period of time, and then the liquid metal thermal interface material is wiped off. Figure 5 is a picture of wiping off the liquid metal thermal interface material. The corrosion tests of the materials prepared in Example 1 and Example 3 on nickel metal respectively correspond to Figure 5 (a) and Figure 5(b), after being placed at room temperature for 5 days and wiping off the liquid metal thermal interface material, the surface of nickel metal remains intact, indicating that the liquid metal thermal interface material prepared in this application has almost no corrosive effect on nickel; the corrosion tests of the materials prepared in Example 1 and Example 3 on aluminum metal respectively correspond to Figure 5 (c) and Figure 5 (d). After being placed at room temperature for 1 day, the aluminum metal has been corroded by the gallium-based liquid metal thermal interface material, while the material prepared in Example 3 has been placed at room temperature for 5 days and the aluminum metal has not been corroded by the liquid metal thermal interface material, and the surface of the aluminum metal remains intact. This experiment shows that when using gallium-based liquid metal thermal interface materials, the surface of aluminum metal devices needs to be protected, and the bismuth-based liquid metal thermal interface material has almost no corrosive effect on aluminum metal devices.
[0116] As Figure 6 shown, the thermal interface materials currently used in high-power electronic devices and the like are mainly thermal conductive greases and thermal conductive gels, and the Pump-out phenomenon will occur in thermal conductive greases and thermal conductive gels. The Pump-out phenomenon refers to the phenomenon that when thermal conductive grease is continuously subjected to thermal cycling or mechanical stress (such as the expansion / contraction of the chip and the radiator) for a long time, it is gradually extruded from the contact interface (similar to "pumping out"), resulting in a decrease in thermal conductivity. This phenomenon is common in high-power electronic devices (such as CPUs, GPUs), especially in environments with large temperature differences or frequent vibrations. How to mitigate and solve the Pump-out phenomenon is the mainstream research direction in the industry. Therefore, the Pump-out phenomenon of the gallium-based liquid metal thermal interface material prepared in this application and traditional silicone grease was tested. The test conditions were as follows: the test equipment was a thermal shock chamber, the low temperature was -40°C, the high temperature was 125°C, and continuous thermal shock was carried out for 14 days. As Figure 6 (a) and Figure 6 (b) shown, the materials prepared in Example 1 and Comparative Example 1 had almost no Pump-out phenomenon, while obvious cracking occurred in the silicone grease in Figure (c). This test shows that the gallium-based liquid metal thermal interface material prepared by the method of this application hardly produces the Pump-out phenomenon.
[0117] The above-described embodiments only represent several implementation manners of the present invention, and the description thereof is relatively specific and detailed, but it should not be construed as a limitation on the scope of the invention patent. It should be noted that for those of ordinary skill in the art, without departing from the concept of the present invention, several modifications and improvements can still be made, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention patent shall be subject to the appended claims.
Claims
1. A thermal interface material with liquid metal dynamic bonds, characterized in that, Comprising the following components in parts by weight: Liquid metal: 50 - 90 parts, thermal conductive filler: 10 - 30 parts, metal filler: 5 - 20 parts, coupling agent: 0.1 - 0.3 parts, The metal filler is used to reduce the interfacial thermal resistance. The surface of the metal filler is modified with a coupling agent. The addition of the coupling agent directionally increases the groups on the surface of the metal filler, increases the number of lone electron pairs, which is beneficial to the formation of dynamic bonds of the liquid metal, increases the interaction force between the liquid metal and the thermal conductive powder, and thus increases the viscosity.
2. The thermal interface material with a liquid metal dynamic bond according to claim 1, characterized in that, The liquid metal is one or more of alloys such as gallium-based, bismuth-based, indium-based, tin-based, etc.
3. The thermal interface material with a liquid metal dynamic bond according to claim 1, characterized in that, The thermal conductive filler is one or more of aluminum nitride, aluminum oxide, zinc oxide, boron nitride, silicon carbide, magnesium oxide, silicon dioxide, calcium carbonate, magnesium sulfate, diamond, boron carbide, silicon nitride, etc., and its particle size is 0.1 - 30 μm.
4. The thermal interface material with a liquid metal dynamic bond according to claim 1, characterized in that, The metal filler is one or more of silver powder, nickel powder, copper powder, aluminum powder, silver-plated aluminum powder, silver-plated copper powder, silver-plated nickel powder, iron powder, etc., and its particle size is 0.5 - 30 μm.
5. The thermal interface material with liquid metal dynamic bonds according to claim 1, characterized in that, The coupling agent is one or more of alkyl siloxane coupling agents, amino siloxane coupling agents, alkyl silicon nitride coupling agents, amino silicon nitride coupling agents, etc.
6. The thermal interface material with a liquid metal dynamic bond according to claim 1, characterized in that, The volume ratio of the liquid metal is 65% - 75%.
7. A preparation method of a liquid metal thermal interface material for preparing the thermal interface material with dynamic liquid metal bonds as described in any one of claims 1 to 6, characterized in that The metal filler is subjected to interfacial modification by a coupling agent, The thermal conductive filler and the metal filler after interfacial modification are mixed and stirred, then the liquid metal is added and mixed and stirred, heated, and stirred under vacuum conditions. After the stirring is completed, the liquid metal thermal interface material is obtained.
8. The preparation method of the liquid metal thermal interface material according to claim 7, characterized in that, It further includes a step of judging whether the thermal conductive filler is qualified. The thermal conductive filler is added to the liquid metal and heated to 10°C above the melting point of the liquid metal, and stirred under vacuum conditions. The stirring time is controlled to avoid spontaneous combustion due to overheating of the mixture. After the stirring time reaches, the mixture is in a paste state and there is no solid-liquid separation, indicating that the thermal conductive filler is a qualified thermal conductive filler.
9. The preparation method of the liquid metal thermal interface material according to claim 7, wherein The interfacial modification of the metal filler by the coupling agent specifically includes: mixing the metal filler, the coupling agent and absolute ethanol, then heating and stirring, and then performing filtration, washing and drying steps.
10. A testing method of a liquid metal thermal interface material, including the thermal interface material with dynamic liquid metal bonds as described in any one of claims 1 to 6, characterized in that The prepared liquid metal thermal interface material is applied on the base, the base is placed in a thermal shock chamber, the low temperature of the test temperature is -40°C, the high temperature is 125°C, and the liquid metal thermal interface material on the base is continuously subjected to thermal shock in the thermal shock chamber for 10 to 20 days.